ACCULTURATION, CULTURE SHOCK AND SOCIAL DISTANCE - Yusupova Moxiniso Dilmurod qizi; Axmedova Muhayyo (Journal of new century innovations, 2023)
Abstract: in today's globalized world, intercultural competence has become an essential skill for individuals to have. Acculturation, culture shock, and social distance are key concepts that play a vital role in developing intercultural competence. This article will explore these concepts in depth and provide strategies for managing them effectively. Understanding and navigating these concepts can help individuals build stronger relationships with people from different cultures and contribute to a more connected and inclusive world.